Transplantation of a three-lobed donor left lung: A case report - Samuel Jacob; Ian A Makey; Magdy M El-Sayed Ahmed; Jorge M Mallea; David B Erasmus; Erol V Belli (SAGE Open Medical Case Reports, 2019)
A true left middle lobe (lingular lobe) is very rare, but accessory fissures can be unexpectedly found at transplant. Pre-transplant knowledge of accessory lobes and accessory fissures aids in preparation, transplantation, postoperative assessment, and long-term care planning; however, fissures and accessory lobes can be overlooked by radiologists during routine evaluation of images. Here, we describe the first left lung with three anatomical lobes that was successfully transplanted into a 63-year-old patient with idiopathic pulmonary fibrosis. This anatomical variation did not change our surgical plan or technique, but surgeons should be aware of this possibility, especially when planning postoperative care.